Clinical and Morphological Features of the New Coronavirus Infection (Covid-19) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The emergence of COVID-19 has posed challenges for healthcare workers to quickly diagnose and provide medical care to patients. Currently, information on the epidemiology, clinical features, prevention and treatment of this disease is limited.